Self-medication among the elderly in Iran: a content analysis study - Seyede Salehe Mortazavi; Mohsen Shati; Hamid Reza Khankeh; Fazlollah Ahmadi; Shiva Mehravaran; Seyed Kazem Malakouti (BMC Geriatrics, 2017)
Abstract Background Self-medication is described as the use of drugs without a physician’s prescription to treat self-recognized illness or symptoms, and an important health issue among the elderly. Despite the wide range of different definitions, recognizing all forms of self-medication among older adults, particularly, in developing countries, help healthcare professionals and providers to reduce harmful effects of self-medication. The purpose of this study is to describe the practice of self-medication and its related factors among elderly people in Iran based on the experiences of people who are involved in this phenomenon. Methods This qualitative study was conducted using content analysis. Purposive sampling was used to select the participants and continued until saturation. The participants were the elderly, their care-givers, physicians, and pharmacists. Data was collected using semi-structured interviews, and analysis was done using an inductive approach. The theory of planned behavior was used as a framework to explain the role of the emerged factors in the occurrence of self-medication behavior. Results Based on the expressed experiences of the participants, factors related to the practice of self- medication among the elderly in Iran fit in these 5 categories: “patient’s attitudes towards disease, treatment, and physicians”, “living with disease”, “unfriendly environments”, “enabling health system”, and “influential others”. Conclusions Based on the results of this study, self-medication of the elderly in Iran has commonalities with many countries in regard to over-the-counter medications and complementary and alternative medicine; however, self-medication is also seen with drugs that require a prescription but can easily be obtained from pharmacies. Contributing factors, apart from the elderly themselves, include their families, caregivers, and social circle, the physical environment where they live, and the health system from which they receive services.